Experimantal researches of the achievements of a current burdening course plates - Tegza, Іvan (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article presents the results of the experimental study of the peculiarities of the work under the calculation load of planarsuperstructural plates of the developed system of non-beating overlap. Great attention is paid to the construction of bearingstructures prototype. The design of auxiliary equipment is described, which enabled to test the investigating U-block in conditionsthat imitate real resistance. The method of performing experimental research with indication of methods and means ofmeasuring geometrical and physical parameters that characterize the stress-strain state and bearing capacity of the test plate isgiven. The conducted investigations enabled to determine the nature of deformation and destruction of the superstructureslabs as a separate element in the developed system of non-beating ceiling. Attention is drawn to the fact that the achievementof the bearing capacity is not accompanied by the process of destruction, but is characterized by significant movementsof the supporting plots in the vertical plane
Keywords: displacement; bearing capacity; deformed state; experimental research; unbounded overlap